IMPROVING STUDENTS’ ABILITY IN WRITING NARRATIVE TEXT BY USING PICTURE SERIES FOR THE EIGHT GRADE STUDENTS OF JUNIOR HIGH SCHOOL - Tuti Andayani; Arono - (Universitas Bengkulu, 2016)
In this collaborative Classroom Action Research (CAR), the researcher tried to overcome the problem of writing narrative text facing by the eighth-grade students in Junior High School, especially in getting and composing the ideas. The question of this research was ‘Can Picture Series improve the students’ ability in writing the narrative text?’ This class action research was divided into two cycles. Every cycle was divided into four stages, including (1) planning, (2) implementing, (3) observing, and (4) reflecting and it was focussed on the students’ ability in writing narrative text by getting idea from a picture and developing the idea with the guidance from a series of pictures. The samples were 20 students of SMP Negeri 03 Sindang Kelingi, Curup, and Rejang Lebong. The data which were got from the students’ achievement in the cycle I and cycle II were analyzed by using quantitative analysis data technique. From the analysis, the writer founded that in the cycle I, students gain the average score 61,35 and in the cycle II the average score was 84,50.It is suggested for the Junior High School English teachers to apply this technique increase their students’ ability in writing the narrative